STUDI PELAKSANAAN PROGRAM CORPORATE SOCIAL RESPONSIBILITY PERUSAHAAN DI WILAYAH KABUPATEN KUTAI KARTANEGARA DAN KOTA SAMARINDA - Jawatir Pardosi (Pusjar SKPP Lembaga Administrasi Negara, 2011)
The study is aimed to analyze: (a) the benefit of CSR programs in improving the community welfare of local community; (b) the matching between CSR programs with the real needs of local community; and c) the matching of the CSR programs with government development program and the effectiveness of government role of implementing the CSR programs. The study used 325 respondents for survey and 15 participants in FGD. Data analysis used the descriptive qualitative, syllogistic, and data comparative. The results of this study showed that: (a) the CSR programs could improved the welfare of local community, (b) the CSR programs have matched with the community real needs in educational, socio-cultural, and infrastructure aspect. However, they do not match the agriculture and economy and (c) the Kukar Government is not effective as a facilitator and regulator in implementing the CSR.Keywords: CSR, community welfare, community real needs, government role.Studi ini bertujuan untuk menganalisis: (a) manfaat program CSR dalam pengembangan kesejahteraan komunitas lokal; (b) kesesuaian program CSR dengan kebutuhan nyata komunitas lokal; dan (c) kesesuaian program CSR dengan program pembangunan pemerintah dan efektivitas peran pemerintah dalam pelaksanaan program CSR. Studi ini melibatkan 325 responden untuk survei dan 15 orang dalam FGD. Analisis data menggunakan deskriptif kualitatif, silogistik, dan perbandingan data. Hasil studi ini menunjukkan bahwa: (a) program CSR dapat memperbaiki kesejahteraan komunitas lokal; (b) program CSR memiliki kesesuaian dengan kebutuhan nyata komunitas dalam aspek pendidikan, sosial budaya, dan infrastruktur, tetapi tidak ada kesesuaian dalam aspek pertanian dan ekonomi; dan (c) Pemerintah Kukar tidak efektif sebagai fasilitator dan regulator pelaksanaan CSR.Kata kunci: CSR, kesejahteraan masyarakat, kebutuhan nyata masyarakat, peran pemerintah.